2016
DOI: 10.1371/journal.pone.0153385
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Deficiencies, the Absence of Information and Caregiver Shortcomings: A Qualitative Analysis of Infant Feeding Practices in Rural China

Abstract: Background and ObjectivesDevelopment during the first two years of life is critical and has a lasting impact on a child’s health. Poor infant and child nutrition can lead to deficiencies in essential micronutrients, which may cause a weakened immune system and lasting effects on children's growth and development. Recent studies in rural Shaanxi Province found an anemia prevalence of 54.3% among rural children aged six to twelve months. While new large-scale, quantitative research has begun to catalogue the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 16 publications
5
50
1
1
Order By: Relevance
“…Objectively, in China, social development regarding the welfare of the elderly, infants, and pregnant women is still very deficient. Both the governmental system and the related market services are inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…Objectively, in China, social development regarding the welfare of the elderly, infants, and pregnant women is still very deficient. Both the governmental system and the related market services are inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 60 percent of China's elementary school children (ages 6 to 12) have at least one health or nutrition problem that can seriously affect early cognitive skill development (Zhou et al 2015).…”
Section: Lagging Human Capital Development For Rural Residentsmentioning
confidence: 99%
“…These left-behind children may be hindered in developing noncognitive and social skills due to the absence of their parents (Zhou et al 2015). Approximately 39 percent of the infants and toddlers (ages 0 to 3) that are born and raised in rural Chinese villages exhibit cognitive or psychomotor delay.…”
Section: Lagging Human Capital Development For Rural Residentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in China reported that the diet given to children lacked food rich in micronutrients as mothers and caregivers do not understand the importance of nutrition. [3] It was indicated by other researchers that children under the age of five years are not fed with adequate variety of food as caregivers lack information related to nutrition. [4] Mothers and caregivers lack information related to nutrition, because they were not provided with such information by the health workers.…”
Section: Lack Of Information Related To Nutritional and Feeding Practmentioning
confidence: 99%